The trader, the owner, the slave parallel lives in the age of slavery - Walvin, James (Jonathan Cape, 2007)
In this new and original interpretation of the barbaric world of slavery and of its historic end in April 1807, the parallel lives of three individuals caught up in the enterprise of human enslavement-a trader, an owner, and a slave-are examined. John Newton (1725-1807), best known as the author of Amazing Grace, was a slave captain who marshaled his human cargoes with a brutality that he looked back on with shame and contrition. Thomas Thistlewood (1721-86) lived his life in a remote corner of western Jamaica and his unique diary provides some of the most revealing images of a slave owner's life in the most valuable of all British slave colonies. Olaudah Equiano (1745-97) was practically unknown 30 years ago, but is now an iconic figure in black history and his experience as a slave speaks out for lives of millions who went unrecorded. All three men were contemporaries; they even came close to each other at different points of the Atlantic compass. But what held them together, in its destructive gravitational pull, was the Atlantic slave system.